Air quality and employee hygiene-related behavior in a post anesthesia care unit in Thailand - Somphorn Kampan (JMIR Publications, 2019)
Post anesthesia care units (PACU) are sanitary spaces at hospitals. Bacterial and fungal contaminants in ambient air can pose significant threats to patient recovery. Excess waste anesthetic gases such as nitrous oxide and desflurane can also pose reproductive, genetic, and other health risks to PACU staff who suffer longterm exposure. Healthcare institutions routinely monitor and study PACU air quality as required by occupational health and safety acts and related regulations, and professional standards of care. This study presents recent data from a PACU intervention at Rajavithi Hospital in Bangkok, Thailand. Rajavithi took measurements of concentrations of airborne fungi, bacteria, desflurane, and nitrous oxide before and after installation of a new ventilation system. Concurrently, the hospital surveyed employees before and after a hazard communication and conducted a training campaign in efforts to understand employee attitudes toward health and safety procedures, and to increase their perceived importance of several PACU-specific protocols. Results showed bacterial contamination fell from 1,307 CFU/m3 to 182 CFU/m3, fungi fell from 70.4 CFU/m3 to 35.8 CFU/m3, desflurane fell from 0.25 ppm to 0.21 ppm, and nitrous oxide fell from 21.86 ppm to 20.47 ppm during the intervention while PACU worker attitudes toward health and safety improved. Additional monitoring, communication, and training are recommended for Rajavithi and other healthcare institutions.